Chinese International Student Sexual Harassment on U.S. College Campuses - Chang, Yunling; Ali, Sakina; Sahu, Ankita; Dong, Sidai; Thornhill, Carly W.; Milian, Polet; Castillo, Linda G. (Journal of International Students, 2021)
The #MeToo movement has brought the issue of sexual harassment to U.S. college campuses. Most scholarly work in this area focuses on White American women with little information on international student experiences. Because sexual harassment is considered hush-hush (shi) and taboo, many Chinese international students may not question harassment behaviors they experience. For many Chinese women attending a U.S. university, their first public discussion may occur during student orientation. Thus, students come to college campuses with varying levels of awareness of sexual harassment. Given the growing number of Chinese international students, the purpose of this article is to provide an overview of their experiences and perceptions of sexual harassment. The article provides recommendations for university personnel working with international students.